O edukacji w zakresie praw zwierząt. Teoria Toma Regana - Probucka, Dorota (Wydawnictwo Naukowe UAM, 2017)
The article concerns a new educational theory based on the idea of animal rights. It was presented and developed by the American ethicist Tom Regan, which drifted its axiological base and was the initiator of socio-educational movement called Animal Rights Movement, to which joined other ethicists, educators, layers, veterinarians, and even theologians. The article contains analysis of Tom Regan's views on the issue of moral status of non-human beings, and consists of two parts. The first part concerns the criticism of ethical theories based on the idea of direct and indirect moral duties to animals. In the second part are discussed the main concepts and principles of a new way of thinking such as: inherent value, a subject of a life criterion, the respect principle and its derivatives.
About Education on Animal Rights. Tom Regan's Theory
Keywords: animal rights; environmental ethics; Tom Regan; moral duties